Reciprocal thinking and its relationship to the courage to exist among university students - Musa Abed Al-Jubouri, Hussein (Journal of College of Education, 2022)
Abstract Reciprocal thinking and its relation to the courage to exist among university students. The current research aims to identify: 1- The degree of reciprocal thinking among university students. 2- the degree of statistical differences in the thinking of exchange among university students according to the variables of sex (male - female) and specialization (scientific - human). 3- the degree of courage for the presence of university students. 4- The statistically significant differences in the courage to exist for university students according to the gender variable (male - female) and specialization (scientific - human). 5- The correlation between mutual thinking and courage for existence To achieve these goals, the researcher built two measures of the first of the reciprocal thinking and the second of the courage to exist, and the honesty and consistency of each of them were extracted, as well as the force of excellence. The two measures were applied to a sample of 400 students who were selected in a simple random manner with proportional distribution and after processing the data statistically And the correlation coefficient and the coefficient T for correlation, correlation coefficient, Pearson correlation coefficient, and regression coefficient, the researcher reached the following results: 1- The university students suffer from weakness in mutual thinking. 2- There are statistically significant differences in the reciprocal thinking among university students according to the gender variable (males and females) and males. There are statistically significant differences according to the variable of specialization (scientific - human) and in favor of human specialization. 3- University students have the courage to exist. 4- There are statistically significant differences in the courage to exist for university students according to the gender variable (male - female) and in favor of females, and there are statistically significant differences in the variable of specialization (scientific - human). 5- There is a weak and non-functional relationship between mutual thinking and courage for existence. The researcher then made a number of recommendations and proposals